Attention Modulates the Role of Speakers’ Voice Identity and Linguistic Information in Spoken Word Processing: Evidence From Event-Related Potentials. - Yunxiao Ma; Keke Yu; Shuqi Yin; Li Li; Ping Li; Ruiming Wang (Journal of Speech, Language & Hearing Research, 2023)
Purpose: The human voice usually contains two types of information: linguistic and identity information. However, whether and how linguistic information interacts with identity information remains controversial. This study aimed to explore the processing of identity and linguistic information during spoken word processing by considering the modulation of attention. Method: We conducted two event-related potentials (ERPs) experiments in the study. Different speakers (self, friend, and unfamiliar speakers) and emotional words (positive, negative, and neutral words) were used to manipulate the identity and linguistic information. With the manipulation, Experiment 1 explored the identity and linguistic information processing with a word decision task that requires participants’ explicit attention to linguistic information. Experiment 2 further investigated the issue with a passive oddball paradigm that requires rare attention to either the identity or linguistic information. Results: Experiment 1 revealed an interaction among speaker, word type, and hemisphere in N400 amplitudes but not in N100 and P200, which suggests that identity information interacted with linguistic information at the later stage of spoken word processing. The mismatch negativity results of Experiment 2 showed no significant interaction between speaker and word pair, which indicates that identity and linguistic information were processed independently. Conclusions: The identity information would interact with linguistic information during spoken word processing. However, the interaction was modulated by the task demands on attention involvement. We propose an attention-modulated explanation to explain the mechanism underlying identity and linguistic information processing. Implications of our findings are discussed in light of the integration and independence theories.